FXRS: Fast X-Ray Spectrum-Simulator Theory and Software Implementation. (26th April 2017) - Chirilă, Ciprian C.; Ha, T. M. H.
Abstract: We propose a simple, computationally efficient scheme for an X-ray spectrum simulator. The theoretical models describing the physical processes involved are employed in our Monte Carlo software in a coherent way, paving the way for straightforward future improvements. Our results compare satisfactorily to experimental results from literature and to results from dedicated simulation software. The simplicity, excellent statistical errors, and short execution time of our code recommend it for intensive use in X-ray generation simulations.